The impact of Brassica oleracea var italica and Capsella bursa pastoris extracts on WISH cancer cells - Khripko, V.; Baranovsky, M. (Problems of Environmental Biotechnology, 2019)
Objective: to investigate the impact of aqueous extracts of Brassica oleracea var italica and Capsella bursa pastoris on the WISH (monolayer) cancer cell line. Chemical composition and pharmacological properties of Brassica oleracea var italica and Capsella bursa pastoris are considered. Methods: this article considers microscopic method based on inhibition and percentage determination of cancer cell lines. Results: experiment shows that Brassica oleracea var italica and Capsella bursa pastoris can be used against cervix cancer cells – human WISH (monolayer) cell line.